Communicating Gender: Construction Of Gender Identities In Selected Malaysian Lifestyle Magazines - Aziz, Surayah Abd (2018)
Since media not only reflects differences between gender roles through its content, but also influences matters on gender with stereotyping. This study examines how six Malaysian women and men’s lifestyle magazines published in the twenty-first century portray gender roles today. Guided by feminist theories, the textual analysis of both Bahasa Malaysia and English language lifestyle magazines of Her World, Wanita, Nona, Maskulin, Glam Lelaki and Men’s Health helps uncover how gender identities are constructed and if these magazines promote stereotypes that uphold a patriarchal system that affects national policies pertaining to women and their progress.